Loss of SynDIG4/PRRT1 alters distribution of AMPA receptors in Rab4- and Rab11-positive endosomes and impairs basal AMPA receptor recycling - He, Chun-Wei; Díaz, Elva (Frontiers in Pharmacology, 2025)
The transmembrane protein Synapse Differentiation Induced Gene 4 (SynDIG4) functions as an auxiliary factor of AMPA receptors (AMPARs) and plays a critical role in excitatory synaptic plasticity as well as hippocampal-dependent learning and memory. Mice lacking SynDIG4 have reduced surface expression of GluA1 and GluA2 and are impaired in single tetanus-induced long-term potentiation and NMDA receptor (NMDAR)-dependent long-term depression. These findings suggest that SynDIG4 may play an important role in regulating AMPAR distribution through intracellular trafficking mechanisms; however, the precise roles by which SynDIG4 governs AMPAR distribution remain unclear. Here, we characterized the endocytosis and recycling of GluA1-containing AMPARs under basal conditions. We did not observe any change in baseline endocytosis; however, we did observe a significant decrease in recycling of GluA1-containing AMPARs in cultured hippocampal neurons from mice lacking SynDIG4. This resulted in a significant increase in the levels of internal GluA1 and GluA2, along with greater colocalization of these subunits with Rab4-positive recycling endosomes. Notably, the overlap between Rab4-positive and Rab11-positive vesicles was elevated in hippocampal neurons lacking SynDIG4, suggesting an impairment in the trafficking between these compartments. Furthermore, our findings revealed a reduction in surface GluA1 within synaptic regions of hippocampal neurons lacking SynDIG4. Collectively, these results indicate that SynDIG4 regulates the distribution of GluA1-containing AMPARs via the Rab4-dependent endosomal recycling pathway, thereby maintaining AMPAR levels at synaptic regions under baseline conditions. This regulatory function of SynDIG4 may contribute to the deficits in GluA1-dependent synaptic plasticity and impairment of hippocampal-dependent behaviors observed in SynDIG4 deficient mice.